Effects of antidiabetic medications on cardiovascular outcomes. Issue 10 (16th September 2020) - Leung, Marco Shiu Tsun; Lin, Shangzhe George; Uthayanan, Leshanth; Harky, Amer
Abstract: Objectives: Hyperglycemia is associated with an increased risk of adverse cardiovascular outcomes, such as heart failure, coronary heart disease, stroke, and in‐hospital mortality. For those receiving cardiac surgery, up to half develop hyperglycemia while 30% have a diagnosis of diabetes, which is defined by chronic hyperglycemia. Due to a prothrombic state and endovascular damage, patients with diabetes have a twofold increased risk of cardiovascular events. Methods: Electronic literature search was done to identify articles that have discussed antidiabetic medications and how it is impacting the glycemia status as well as cardiovascular outcomes. No limits were placed on timing of the publication or type of the article. Key words and MeSH terms were used to conduct the search and the results are summarized in a narrative manner within each relevant section. Results: Antidiabetic medications play a key role in lowering blood glucose levels to reduce adverse cardiovascular outcomes. However, it is a challenge to assess their cardiovascular safety due to confounding factors, such as age, obesity, smoking, hyperlipidemia, and high blood pressure. Further research in this field is required to understand this correlation closely. Conclusion: Optimizing blood glucose level during the perioperative period with correct medication and dose have a significant role in reducing morbidities. Measures should be taken to provide a safe blood glucose level for optimum outcomes.